Investigation on combustion derived BaMgAl10O17:Eu2+ phosphor powder and its corresponding PVP/BaMgAl10O17:Eu2+ nanocomposite - Pradal, Nathalie; Chadeyron, Genevieve; Therias, Sandrine; Potdevin, Audrey; Santilli, Celso Valentim [UNESP]; Mahiou, Rachid (Royal Soc Chemistry, 2014)
This work focuses on the study of BaMgAl10O17:Eu2+ (BAM:Eu) nanophosphors prepared by a microwave-assisted combustion procedure and more especially on the polymer/BAM:Eu nanocomposite film suitable for optical devices such as solid-state-lighting. Powder presented a specific nanomorphology, highly friable and thus easily ground into fine particles. They were then homogeneously dispersed into a polymer solution (poly(N-vinylpyrrolidone) or PVP) to elaborate a polymer phosphor nanocomposite. The structural, morphological and optical features of the nanocomposite film have been studied and compared to those of a pristine PVP film and BAM:Eu powder. All the characterizations (XRD, SEM, SAXS, etc.) proved that the blue phosphor nanoparticles are well incorporated into the polymer nanocomposite film which exhibited the characteristic blue emission of Eu2+ under UV light excitation. Furthermore, the photostability of the polymer/phosphor nanocomposite film has been studied after exposure to accelerated artificial photoageing at wavelengths above 300 nm.